Processed Multibeam Sonar Data (version 1) from the Southern Ocean acquired during Nathaniel B. Palmer expedition NBP0008 (2000) ... - Jacobs, Stan (Interdisciplinary Earth Data Alliance (IEDA), 2003)
This data set was acquired with a SeaBeam Instruments model 2112 multibeam sonar system during Nathaniel B. Palmer expedition NBP0008 conducted in 2000 (Chief Scientist: Dr. Stan Jacobs). These data files include Acoustic Backscatter, Sidescan, Swath Bathymetry data and were processed at sea using the open source MB-System multibeam sonar processing software. Data were acquired as part of the project(s): Shelf and Bottom Water Formation Near East Antarctic Polynyas and Glaciers; Circumpolar Deep Water and the West Antarctic Ice Sheet, and funding was provided by the U.S. National Science Foundation. ...